2019
DOI: 10.1016/j.ejmech.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and pharmacological attributes of piperine: A bioactive ingredient of black pepper

Abstract: 35 Plants are vital for the wellbeing of humankind in a variety of ways. Some plant extracts contain 36 antimicrobial properties that can treat different pathogens. Most of the world's population relies 37 on medicinal plants and natural products for their primary health care needs. Therefore, there is a 38 growing interest in natural products, medicinal plants, and traditional medicine along with a 39 desire to design and develop novel plant-based pharmaceuticals. These plant-based 40 pharmaceuticals may addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 102 publications
0
48
0
2
Order By: Relevance
“…Piperine may be naturally extracted from black pepper, with a 6% to 13% yield. Despite its many healthy properties, the use of piperine in human health is still limited due to its scarce availability and low solubility in water [ 40 , 41 ]. However, piperine has been shown to be a resveratrol booster, since the oral administration of a formula of piperine plus resveratrol (10/100 mg/kg, respectively) increases the bioavailability of resveratrol by 1544% when compared to resveratrol alone [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Piperine may be naturally extracted from black pepper, with a 6% to 13% yield. Despite its many healthy properties, the use of piperine in human health is still limited due to its scarce availability and low solubility in water [ 40 , 41 ]. However, piperine has been shown to be a resveratrol booster, since the oral administration of a formula of piperine plus resveratrol (10/100 mg/kg, respectively) increases the bioavailability of resveratrol by 1544% when compared to resveratrol alone [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its fruits are popularly used as a hot and pungent spice for flavoring food. Its fruits are usually dried and used as spices and seasonings [ 158 , 159 ]. Black pepper is also used to produce pepper oil and oleoresin, for the production of foods and also for perfumery [ 156 , 157 , 160 ].…”
Section: Bioactive Compounds From Eos Of Spice Plantsmentioning
confidence: 99%
“…Over the last twenty years, numerous studies have shown that many natural products display chemoprotective properties against different types of cancers [1,2]. In this context, piperine (a trans-trans isomer of 1-piperoyl piperidine) (Figure 1), the pungent amide present in Piper spices, such as the widely used black pepper (Piper nigrum L.,) is known to present a broad spectrum of biological activities, including its anti-cancer effect [3][4][5]. Regarding the multidrug resistance (MDR) phenotype, a serious obstacle for the treatment of cancer patients [6], previous studies have demonstrated that piperine inhibits the activity of the main ABC transporters related to MDR phenotype [7,8].…”
Section: Introductionmentioning
confidence: 99%